Psoriasiform Digital Bowen’s Disease: A Diagnostic Challenge and Short-Term Response to Liquid Nitrogen Cryotherapy - Putu Resika Melarosa; Ketut Kwartantaya Winaya; Lettisia Amanda Ruslan; Made Sri Adnyasitarini; Putu Ayu Paramitha Saraswaty (HM Publisher, 2026)
Background: Bowen’s disease (BD), or squamous cell carcinoma in situ, classically presents as a slowly enlarging erythematous plaque on sun-exposed skin. However, digital Bowen’s disease represents a distinct and rare clinical subset that frequently poses a significant diagnostic dilemma. Due to its unique anatomical location and morphological variability, digital BD often masquerades as benign inflammatory dermatoses, particularly psoriasis or chronic eczema, leading to dangerous therapeutic delays. Case presentation: We report the case of a 46-year-old male presenting with a solitary, rough, erythematous plaque on the dorsal aspect of the left index finger that had persisted for one year. The lesion was initially misdiagnosed and treated as an inflammatory condition without success. Detailed dermoscopic evaluation revealed a specific